The Interrelationship betweeen Motivation, Organizational Culture and Engagement.The Next Challenge for 21st Century Leaders - Eli Laniado (Institute of Economic Research (IER), 2017)
Research background: The huge research interest in the interrelationship between motivation, organizational culture, and engagement can be explained psychologically and economically. Psychological reasons include work individualization, increasing interest in positive psychology, and the role of human resources, perceived as a key resource in enhancing business competitive advantage. The economic reason is 'engagement deficit' resulting from low employee engagement rates in organizations. Business organizations around the world pay a heavy price for unengaged and uncommitted employees. Leaders today are exerting tremendous pressure on their workforces to achieve optimal results. It is, therefore, becoming increasingly important for organizations to attract, engage, develop and build loyalty among their employees, based on their organizational culture, to gain a competitive edge in today's global marketplace. Purpose of the article: The article's main purpose is exploring the interrelationship between three variables: motivation and organizational culture, which are independent variables, and engagement which is the dependent variable. This is important in the light of 21st century leaders' challenges to establish a solid organizational culture to engage their employees. Methodology: Methodology is based on a multidisciplinary literature review in the fields of organizational psychology and management theory, including nearly 100 articles, reports and books. Findings: Building an engagement organizational culture means leaders must understand the interrelationship between organizational culture and engagement and its contribution to achieving business goals. Managing organizational culture requires leaders to focus on human aspects like motivation and employee values. The engagement organizational culture lies, profoundly, at the center of the ethical value-based organizational culture.
Keywords: J24; M54; 330; motivation; engagement; organization culture; empowerment; leadership